Neoformação vascular, densidade linfática e expressão dos fatores de crescimento vascular A e c em carcinomas mucoepidermóides de glândulas salivares menores - Frederico Omar Gleber Netto (2011)
Mucoepidermoid carcinoma (MEC) is the most common malignant tumor of salivary glands. This tumor is characterized by a great variability in clinical behavior, and there is no entirely reliable method to determine prognosis of this tumor. Angiogenesis is an important step in tumor progression and is believed to be an essential event for metastatic dissemination. We aimed to investigate the role of angiogenesis in MEC through immunohistochemical evaluation of VEGF-A, VEGF-C and D2-40 proteins and measuring the density of neoformed and lymphatic vessels. We studied 26 cases of MEC, which showed great angiogenic activity measured by neoformed vessel density. However, a low density of lymphatics was observed. VEGF-A, VEGF-C and D2-40 were commonly detected in MEC, but only VEGF-A expression correlated with neoformed vessel density. Recurrence and nodal metastasis were associated with low VEGF-A expression and low neoformed vessel density, indicating that impaired angiogenesis could lead to an aggressive phenotype. Although angiogenesis seems important in the modulation of MEC comportment, none of the parameters analyzed could predict tumor behavior.